Ødemarken – Det herreløse land: Knut Hamsuns Markens Grøde (1917) og Stina Aronsons Hitom himlen (1946) som nordlige naturtekster - Reed, Beatrice M. G. (Nordlit, 2020)
The article examines the relationship between man and nature in Knut Hamsun’s Growth of the soil (1917) and Stina Aronson’s This Side of Heaven (1946). Combining an ecocritical and a postcolonial perspective, a set of ideologically charged notions associated with the northern wilderness come in to light. Through depictions of farmers, landscapes, animals, Sámi characters and supernatural elements, the analysis highlights both anthropocentric and colonial tendencies as well as a questioning of the perceived power structures between these actors. Thus, the article can also be regarded a contribution to an ongoing discussion of Hamsun’s controversial Nobel Prize-winning novel as an ecological text. The comparative and situated approach helps widen the ecocritical perspective, especially regarding the status of the Sámi in the text.